Synthesis and Structural Characterization of Palladium(II) Complex Bearing N-Heterocyclic Carbene - Gökçe, A.G.; Türkmen, H.; Aygün, M.; Çetinkaya, B.; Büyuk̈güngör, O. (Springer/Plenum Publishers, 2008)
Trans-Bis[1,3-bis(2,4-dimethylphenylimidazolidin-2-ylidene)] dichloropalladium(II), 4, was prepared from 1,3-bis(2,4-dimetilphenyl) imidazoliniumchloride. The crystal and molecular structure of 4 have been determined by single crystal X-ray diffraction. The title compound, C 38H44N4PdCl2, crystalizes in the monoclinic space group P 21/n with a = 13.8713(9) Å, b = 12.1365(6) Å, c = 21.5499(15) Å. The Pd atom has a slightly distorted square planar coordination geometry. The molecules of the title compound are linked by C-H⋯Cl weak hydrogen bonds into two-dimensional sheets parallel to the (001) plane. In addition, the title compound was characterized by elemental analyses and NMR spectroscopy. © 2008 Springer Science+Business Media, LLC.
Keywords: Crystal Structure; N-Heterocyclic Carbene; Palladium(II) Complex